PENANAMAN KARAKTER RELIGIUS DALAM PENDIDIKAN KEPRAMUKAAN DI SEKOLAH DASAR BANYUKUNING - Kurnia Fatmawati (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
The gap between educational practice and student character that occurs requires serious, special and consistent attention from various parties. This is because the world of education in Indonesia can now be said to be entering a complicated period. The disbursement of a large education budget is accompanied by various breakthrough programs such as not being able to solving fundamental problems in the world of education, namely how to produce superior educational alumni who are faithful, pious, professional, and with character. The purpose of this research is to examine scouting activities that value religious character, the role of scouting education in instilling religious character in elementary schools, and what factors play a role in cultivating religious character through scouting education. With a descriptive qualitative approach through interview techniques, documentation, and observation. From this study it was found that we can make Scouting Education as a medium or place for developing and cultivating character in students, especially in the religious or religious field.